5. STUDY ON CLINICAL, PARA-CLINICAL CHARACTERISTICS AND EVALUATION OF EARLY RESULTS OF TREATMENT OF NON-MUSCLE INVASIVE BLADDER CANCER AT CAN THO FROM 2021 TO 2023 (Vietnam Journal of Community Medicine, 2024)
Aim: (1) Survey of clinical and paraclinical characteristics of non-muscle invasive bladder cancer at Can Tho Central General Hospital in 2021-2023; (2) Evaluate early results of treatment for nonmuscle invasive bladder cancer at Can Tho Central General Hospital in 2021-2023. Methods: Descriptive retrospective combined with prospective studies on 45 patients aged 16 years and older with non-muscle invasive bladder cancer treated at Can Tho Central General Hospital from January 2021 to December 2023. Results: Men account for a high proportion of 88.89%. The age group with the highest percentage is the group from 61 - 80 years old, accounting for 62.22%. Symptoms of mild anemia account for 20%. There are 97.78% of ultrasound cases that detect tumors through ultrasound. Tumor size on ultrasound and abdominal CT-Scan are 81.82% similar. Bladder tumors at stage Ta account for 55.56%, with G1 differentiation accounting for 62.22%. Side effects of burning and painful urination accounted for 13.33% and side effects of pain in the lower abdomen accounted for a low rate of 2.22% after adjuvant treatment with Doxorubicin. Surgical results: mostly good results 95.56%, no cases of bad results. Conclusion: Laparoscopic resection of non-muscle invasive bladder tumors through the urethra is a safe method and should be widely applied in Can Tho.
Keywords: Non-muscle invasive bladder cancer, endoscopic ablation, adjuvant chemotherapy.